Culture-Centric Vs. Person-Centered Cultural Psychology and Political Philosophy. (6th April 2016) - Ratner, Carl
Abstract : My work in cultural psychology – i.e., sociocultural theory – has two branches. One is the study of psychological phenomena as cultural phenomena. The other is the study of the discipline of cultural psychology as a cultural phenomenon. By this I mean the concepts and methods and interventions that the discipline employs, and the cultural factors that shape them. The discipline of cultural psychology is as culturally shaped as the psychology of the people it studies. It can be as culturally mystified as the psychology of the people it studies.